In Reunion and Seychelles Creole languages, the « i » word questions the African substrate hypothesis - (:unkn) unknown (My University, 2019)
Among French-based Creole languages, Reunion and Seychelles Creoles are exceptions in that both languages possess a morpheme i (pronounced « ee »), which has been analysed in various and contradictory ways. We aim to look at this distinctive characteristic besides the discussion about Creole genesis. In this discussion some scholars claim that these languages are the product of a process of relexification of an African (grammatical) substrate with French lexical items. Our research will lead us to take into account the morpheme a in two African languages, which plays a role similar to i in Reunion and Seychelles Creoles. We choose to name these two morphemes « preverbal markers », so as to show how this obvious similarity between some European Creole and African languages invalidates the substratum hypothesis. In counterpart, we will see –if needed– how this similarity proves that the evolution of Indian Ocean Creole languages conforms to internal and universal principles, exactly like any other human language.
Keywords: African Research